(untitled) (Bangladesh Journal of Microbiology, 2010)
Although the involvement of intestinal bacteria in the degradation of lignocellulosic materials is poorly understood xylanolytic activity of termite has been studied extensively. The present study was designed to identify potential xylanolytic bacteria from termite intestine and the isolated bacterium was studied with a view to preparing low cost medium and optimizing the cultural conditions in Dubos liquid medium. The bacterium produced highest activity of the enzyme (0.86 U/ml) on birchwood xylan as carbon substrate. Wheat bran a relatively cheap lignocellulosic material was found as good inducer of the enzyme. When grown on 4% wheat bran in Dubos liquid medium with an initial pH 6.0 under shaking incubation at 200 rpm at 40°C for 24 h, the bacterium produced the maximum activity of the extracellular xylanase (1.5 U/ml). These results strongly indicated that the bacterium from the intestine in termite is able synthesize xylanase activity on various substrate and the enzyme production can be increased by optimizing the overall cultivation parameters. Keywords: Xylanase; Termite intestinal bacteria DOI: http://dx.doi.org/10.3329/bjm.v25i2.4874 Bangladesh J Microbiol, Volume 25, Number 2, December 2008, pp 123-127